Global Educational Collaboration and Its Role in Elevating Arabic Language Teaching Standards in Postgraduate Studies - Hijjah, Shifany Maulida; Raswan, Raswan; Royani, Ahmad (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
Global educational collaboration has become a cornerstone for improving academic standards across disciplines, including Arabic language teaching in postgraduate studies. This study examines the role of international university partnerships in elevating curriculum standards, teaching methodologies, and graduate outcomes within Arabic language education programs. Using a qualitative approach with case study design to understand the effect of international cooperation in improving the curriculum standards of Master of Arabic Education (MPBA) at UIN Jakarta. Data were collected from interviews with academic leaders, surveys of postgraduate students, and analysis of institutional documents across three universities actively engaged in global collaborations. The findings reveal that partnerships facilitate the exchange of innovative pedagogical practices, alignment with international language competency frameworks, and the introduction of cutting-edge educational technologies. These collaborations also enhance faculty capacity through joint research and professional development programs, leading to a more robust curriculum that meets global academic standards. However, challenges such as cultural differences, resource disparities, and administrative hurdles are noted, requiring strategic policy interventions. This research highlights the transformative potential of international collaboration in modernizing Arabic language postgraduate programs and underscores its significance in preparing graduates for competitive global markets.